PENENTUAN KONSTANTA PASUT LAUT DI WILAYAH PERAIRAN SIBOLGA DARI DATA TOPEX/POSEIDON (1992 - 2002) DENGAN MENGGUNAKAN METODE ANALISIS HARMONIK - Rahmad Daeli, Wira
Ocean tide information is required in most satellite altimetry data processing. In this case, global tide models are usually used for example FES 2004 with 10 constituents, excluding Sa and Ssa constituents. In general, such a model is fit to the tide phenomena in deep ocean areas. This research attempts to compute the same tidal constituents as in the FES 2004 based on Topex/ Poseidon data. Twelve constituents including Sa and Ssa, are also computed. The results shows that the estimated value of 10 constituents are close to the constituents contained in the FES2004 model. On the other hand, the quality of the estimated 12 constituents are better than constituents in FES 2004.